2011
DOI: 10.1111/j.1365-2672.2011.04969.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in spinach phylloepiphytic bacteria communities following minimal processing and refrigerated storage described using pyrosequencing of 16S rRNA amplicons

Abstract: Aims:  To investigate the changes in bacterial diversity on fresh spinach phyllosphere associated with storage at refrigeration temperatures. Methods and Results:  Community structure and population dynamics of spinach phylloepiphytic bacteria associated with packaging and refrigeration of ready‐to‐eat fresh produce were evaluated using pyrosequencing of 16S rRNA gene amplicons. A diverse community responsive to storage at refrigerated temperatures was detected belonging to over 1000 operational taxonomic unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
109
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(138 citation statements)
references
References 54 publications
24
109
3
2
Order By: Relevance
“…This is consistent with previous studies of bacterial communities on leafy greens (11,(13)(14)(15)30). Our results showed that Proteobacteria and Bacteroidetes were the most abundant phyla at harvest.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with previous studies of bacterial communities on leafy greens (11,(13)(14)(15)30). Our results showed that Proteobacteria and Bacteroidetes were the most abundant phyla at harvest.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with the findings of Jackson et al (11). However, Firmicutes replaced Bacteroidetes as one of the dominant phyla in other surveys of the leafy-green phyllosphere (13)(14)(15).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…2). Similar to other studies of edible leaf communities (27,37), Pseudomonadales (primarily Pseudomonas) was the most dominant taxon observed on leaf surfaces. While on average they represented 46% of the bacteria on leaves, their proportion on individual leaf samples varied widely, ranging from 4 to 86%.…”
Section: Resultssupporting
confidence: 83%
“…This method of determining the composition of bacterial communities has been applied to surfaces of ready-to-eat vegetables, including spinach (10)(11)(12)(13). Using such an approach to determine the presence of foodborne pathogens in the bacterial community associated with fresh bagged leafy greens may provide the ability to detect pathogens more quickly than current methods permit.…”
mentioning
confidence: 99%